The Transformation of Legal Consciousness: From Unregistered to Official Marriages in PekorenVillage, Rembang, Pasuruan, East Java - M. Harir Muzakki; Fira Mubayyinah; Muhtar Said; Raihanah binti Abdullah; Khoirul Fathoni; Ali Akhbar Abaib Mas Rabbani Lubis (Universitas Islam Negeri Raden Intan Lampung, 2026)
Although marriage registration occupies a central position in Indonesian family law, unregistered marriage practices persist and, in certain contexts, are even socially normalized. This article examines the transformation of legal consciousness regarding marriage registration in Pekoren Village, Rembang District, Pasuruan Regency, East Java, an area previously known as a hotbed of unregistered marriages. Using a socio-legal approach, this research is based on longitudinal fieldwork conducted between 2021 and 2024,including in-depth interviews, continuous observation, and document analysis involving village officials, religious leaders, and civil society actors. The findings show that the decline in unregistered marriages in Pekoren was not the result of coercive law enforcement or criminalization, but rather a gradual rearticulation of legal consciousness. This transformation was mediated by village-level prohibitions, social sanctions, administrative routines, and the strategic repositioning of religious authorities. Marriage registration is then understood not merely as an administrative obligation, but as a morally legitimate and socially important practice for protecting women, children, and family dignity. Over time, compliance with state marriage law has become customary and accepted as normal in everyday life. This study contributes to socio-legal studies by showing that legal compliance emerges as a relational and processual outcome of “everyday legality” in the context of legal pluralism, and it has implications for family law reform, particularly in formulating policies to combat unregistered marriages that emphasize community mediation and ethical legitimacy rather than a repressive approach